Comparison of Efficacy of Single Application Topical 5% Permethrin versus Single Dose Oral Ivermectin in the Treatment of Scabies - Rao Muhammad Tahir Sattar, Naveed Akhtar Malik, Umair Riaz, Abrar Ahmad Khalid, Ismat Jabin, Furqan Khan Warraich (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To compare the efficacy of a single application of topical 5% permethrin versus a single dose of oral ivermectin in the treatment of scabies. Methodology: Randomized controlled trial. Department of Dermatology, Pak Emirates Military Hospital (PEMH), Rawalpindi, from January 1, 2021, to June 30, 2021. Sixty scabies patients of both genders were included. 30 patients for 5% permethrin cream (group A), and 30 patients for the oral ivermectin group (group B). Follow-up with patients was done at weeks 1 and 2 after treatment. Age in this study was > 5 years. Results: The mean of age was 27.700±8.43 years, duration of disease was 5.133±1.71 weeks, and weight was 71.366±11.31 kg in Group A, while in Group B, age was 30.366±9.37 years, duration of disease was 4.700±1.55 weeks, and weight was 73.433±10.82 kg. Efficacy was observed in 22 (73.3%) patients in group A and 21 (70%) patients in group B (P = 0.775). Conclusion: There is no significant efficacy difference between topical permethrin and oral ivermectin in treatment of scabies. Keywords: Efficacy, Permethrin, Ivermectin, Scabies